A Cinematic Narration Of The Great Depression: Recalling John Ford’s The Grapes Of Wrath - Yılmazok, Levent (The Turkish Online Journal of Design Art and Communication, 2014)
John Steinbeck’s novel The Grapes of Wrath, published in 1939, depicts the poverty of 1930s America during the “Great Depression” through the tragedy of the Joad family, who lost their home and land in Oklahoma and have to drive to California in the hope of finding employment and plenty like many other farmers. The novel was adapted for the cinema the same year and directed by John Ford. Proving welcome in cinema circles and taking its place as a master work in film history, it was one of the few films with radical political connotations hitherto produced by Hollywood. Nevertheless, this cinematic version of the Great Depression narrative has not escaped criticisms, which have been aimed chiefly at aspects of its content that diverge from its parent work. Compared with the novel, the film has been considered more conservative and optimistic, on the grounds that, although the novel emphasizes the class conflict and portrays the Joads as only one of the many suffering families, the film exerts a redundant focus on the family and commends family values: divergences considered to be supported by the visual style of the film. In this article, while recalling Ford’s The Grapes of Wrath, I revisit the above-mentioned criticisms and reassess them in relation to the parenting novel. In doing so, this article also aims to evoke the ongoing economic recession that influences the masses all over the world and the recurrent, unchanging and inevitable outcomes that such crises of capitalism bring for its victims.
Keywords: The Grapes of Wrath; John Ford; Film; Visual Style; Adaptation; Gazap Üzümleri; Görsel Stil; Uyarlama